2018
DOI: 10.1021/acs.jpcc.8b02436
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Dual-Frequency Two-Dimensional Vibrational Spectroscopy of Thin Layers at an Interface

Abstract: The development of spectroscopic approaches to study molecules at interfaces is important as the molecular properties often differ from those in the bulk. Implementation of surface-enhanced two-dimensional infrared (SE 2DIR) spectroscopy using lithographically fabricated plasmonic nanoarrays is demonstrated for nanometer thick films. The sample, 4-azidobutyrate-N-hydroxysuccinimide ester (azNHS), dispersed in polystyrene was deposited onto the nanoarray. Raw enhancements in the SE 2DIR spectra exceeding 5 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…SEAR 2D IR spectroscopy builds from previous work that allows for surface sensitive 2D IR spectroscopy. [24][25][26][27][28][29]32,33 Here, the combination of a reflection geometry and localized surface plasmons effectively decreases the local oscillator intensity while also increasing the third-order signal, providing enhancements of the measured ∆OD of the amide I mode of a peptide monolayer. Table II outlines the signal enhancement observed from the localized surface plasmon, the inverted reflection geometry, and the total enhancement of SEAR 2D IR signals for cys-ovispirin-1 on 3 nm Au/CaF 2 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…SEAR 2D IR spectroscopy builds from previous work that allows for surface sensitive 2D IR spectroscopy. [24][25][26][27][28][29]32,33 Here, the combination of a reflection geometry and localized surface plasmons effectively decreases the local oscillator intensity while also increasing the third-order signal, providing enhancements of the measured ∆OD of the amide I mode of a peptide monolayer. Table II outlines the signal enhancement observed from the localized surface plasmon, the inverted reflection geometry, and the total enhancement of SEAR 2D IR signals for cys-ovispirin-1 on 3 nm Au/CaF 2 .…”
Section: Discussionmentioning
confidence: 96%
“…[24][25][26] Others have used gold nano-antennas to obtain even larger signals through on-resonant enhancement, albeit not in an ATR geometry. [27][28][29] In Hamm's surface enhanced 2D ATR IR spectroscopy, a nanostructured layer of gold coats the surface of a prism that acts as one face of the sample cell. These gold nanostructures have a maximum plasmon absorption in the visible region that extends into the mid-IR.…”
Section: One Approach That Increases Ementioning
confidence: 99%
See 2 more Smart Citations
“…30 A recent paper by Mackin et al demonstrated the utilization of SEIRA principles in two-dimensional IR (2DIR) (surface enhanced 2DIR spectroscopy, SE-2DIR) to study thin layers of materials down to 1 nm. 31 A key advantage of 2DIR is the ability to probe cross peaks or changes that occur in the IR spectrum not in the region actively being pumped that can be linked to molecular structures and their dynamics. However, in SE-2DIR, cross-peak analysis can be problematic, as the cross peaks are typically several orders of magnitude weaker than the diagonal peaks.…”
Section: ■ Plasmonicsmentioning
confidence: 99%